My survival : a girl on Schindler's list - Finder, Rena, 1929-; Greene, Joshua, 1950- (Scholastic Press, 2020)
The author describes how she was eleven years old when the Nazis forced her and her family into the ghetto in Krakow, Poland, during World War II. Then she and her mother were placed on Oskar Schindler's list of factory workers along with 1,200 Jews and kept alive until they were sent to the Auschwitz concentration camp. Finally, it was Schindler who was able to save them from the Holocaust once more. Includes photographs from the author's personal collection and the time period.